The Model of Domestic Product Quality Syndrome - I Gede Mahatma Yuda Bakti; Sik Sumaedi; Tri Rakhmawati; Sih Damayanti; Medi Yarmen (SAGE Open, 2020)
This paper aims to develop and test a model that involves consumer ethnocentrism, world-mindedness, patriotism, and domestic product quality syndrome. This research used a quantitative approach. Data were collected through a survey of 222 respondents in Jakarta, Indonesia. The respondents are consumer electronic product users. Structural equation modeling (SEM) analysis was used to test the conceptual model and hypotheses. The results of this research show that the conceptual model has a good fit. We found that consumer ethnocentrism has a positive and significant impact on domestic product quality syndrome. We also found that patriotism significantly influences consumer ethnocentrism, while world-mindedness does not significantly influence consumer ethnocentrism. Data were collected only in Jakarta. Furthermore, a convenience sampling technique was applied. Thus, the findings of this research may not be generalized to other contexts. Therefore, future studies involving larger respondents coming from diverse areas are required to improve the generalization of the results and examine the stability of this research’s findings. Company should align its strategy and quality objectives with the level of consumer ethnocentrism and patriotism to overcome domestic product quality syndrome. There is a lack of research that develops and tests a model that can be used to explain the phenomenon of domestic product quality syndrome. This research fulfills the literature gaps.